(untitled) (European Journal of Education and Psychology, 2015)
Using a computerized task as an assessment procedure may have advantages over the pencil-and-paper traditional way. The motivational variable associated to computerized tasks can involve a higher functionality results. Computerized tool also can measures a higher range of variables such as response time, error and correct responses, etc. We present the Early-Numeracy-Test-R adapted from a paper and pencil assessment tool. In a multimedia environment, we assessed several components involved in the development of mathematical competence in school- age children of 4-7 years. This kind of measurement provides information about the relational and cognitive components implicit in early mathematical development. It also allowed prediction for children in risk of mathematical learning difficulties. This may encourage processes of prevention and early intervention of mathematical learning difficulties. In this study we present preliminary data of the standardization process.